Roads Leading Out and In: the Legacy of Inmigration - Acuña Trabazo, Ana; Márquez Rodríguez, María Luísa; Dourado Campos, María Xosé (Madrygal. Revista de Estudios Gallegos, 2017)
“Camiños de ida e volta” has its origins in Luis Seoane high school and it bridges the gap between Cuba (La Habana, Santa Clara) and Argentina (Buenos Aires, Río Ceballos, Capilla del Monte, Córdoba). It was born with the objective of giving answer to the alienation of a group of students who were once forced by their parents to leave their countries and school and were brought to Galicia. Galicia is for them a familiar land, for their grandparents’ memories and their involvement in the different events held by the Galician centres in which their families took part. This soon led to the recovery of a very important part of Galician history through family stories. Tales collected with the diaspora protagonists’ voices or their descendants, the chance they gave us to digitize pictures, documents kept for decades (passports, work permits, birth certificates, etc) became a treasure in our high school archive. With work we get to know patrimonial elements (gastronomy, music, craftwork, legends, sayings...) preserved and which entail an important part of the cultural identity of the reception countries. Besides, we had the opportunity to know a lot more about Luis Seoane in Buenos Aires, above all about his muralist production.